THE EFFECTIVENESS OF USING THE MEMRISE GAME FOR STUDENTS’ ENGLISH VOCABULARY - Sa’diah Qotrunnada; Moh. Arifin; M. Labib Al Halim (FKIP, Universitas Billfath Lamongan, 2024)
This research was intended to determine the effectiveness of the Memrise game on English Vocabulary Mastery of MA ALMUHTADI MA students. This research was conducted 10 times which included an observation, a pre-test at the beginning, treatments and a post-test at the end. This research was conducted in Tenth-grade MA ALMUHTADI with a total of 26 students. In this research, researcher used a quantitative model with a pre-experimental approach. The results of the pre-test and post-test were then processed for data normality with the Kolmogorov-Smirnov test. Based on the Kolmogorov-Smirnov test, the data was normally distributed. Then use the sample T-test to determine Sig. Based on the results of the T test, significant p (0.000) < ? (0.05). Due to the significant value was lower than 0.05, there was not enough evidence to reject the null hypothesis (H0), the alternative hypothesis (Ha) was accepted. This means that the students' vocabulary mastery was significantly better after receiving the treatment. It was indicated that learning vocabulary through memrise games was effective for increasing students' vocabulary mastery.